Dry Electrode

By using micro-replicated conductive particles and support layers, the discontinuous conductive particles layer is formed, which solves the problem of electrical signal conduction of dry electrodes in the absence of electrolyte gel, and realizes efficient and low-cost biopotential measurement, simplifies manufacturing Craft.

CN113164121BActive Publication Date: 2024-12-17SOLVENTUM INTELLECTUAL PROPERTIES CO
View PDF 25 Cites 0 Cited by

Patent Information

Application Number
CN201980074486.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-11-13
Filing Date
2019-10-28
Publication Date
2024-12-17
Estimated Expiration
2039-10-28

AI Technical Summary

Technical Problem

When existing dry electrodes are attached to the skin without using an electrolyte gel, it is difficult to achieve effective electrical signal conduction, and the manufacturing process is complex and costly, limiting its wide application on the market.

Method used

Micro-replicable conductive particles prepared by continuous process are coated with redox materials to form discontinuous conductive particles and contact the conductive substrate through the support layer and electrical connector to form dry electrodes, simplifying the manufacturing process and reducing cost.

Benefits of technology

It realizes effective biopotential measurement without using hydrogel, improves the stability and service life of the electrode, reduces production costs, and is relatively simple and easy to perform.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113164121B_ABST
    Figure CN113164121B_ABST
Patent Text Reader

Abstract

The present invention discloses a dry electrode, which is an electrode that is attached to human skin without skin preparation or the use of electrolyte gel. The electrode includes: a substrate; conductive particles, the conductive particles having at least one point, the conductive particles contacting the substrate; a support layer, the support layer encapsulating the conductive particles, the conductive particles having points protruding from the support layer; and an electrical connector. Some electrodes have a conductive substrate, and other electrodes have a conductive support layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure generally relates to dry electrodes - electrodes that attach to human skin without skin preparation or the use of electrolyte gel, and to methods for making these dry electrodes. Background Art

[0002] Electrodes for measuring biopotentials are widely used in modern clinical and biomedical applications. These applications cover many physiological tests, including electrocardiogram (ECG), electroencephalogram (EEG), impedance tomography (EIT), electromyography (EMG), and electrooculography (EOG). Electrodes used for these types of physiological tests act as transducers by converting the electrical potential or biopotential in the body into a voltage that can be measured by conventional measuring and recording devices. Summary of the invention

[0003] The present disclosure relates to dry electrodes - electrodes that attach to human skin without skin preparation or the use of electrolyte gel. Disclosed herein are dry electrodes, sheet article precursors for making dry electrodes, and methods for making these dry electrodes.

[0004] In some embodiments, the electrode includes: a conductive substrate having a first major surface and a second major surface; a discontinuous conductive particle layer, at least some of the conductive particles are in contact with the second major surface of the conductive substrate, and include shaped particles having at least one point. The electrode also includes a support layer, the support layer having a first major surface and a second major surface, wherein the first major surface of the support layer is in contact with the second major surface of the conductive substrate, and the support layer encapsulates the conductive particles so that at least one point of at least one of the conductive particles protrudes from the second major surface of the support layer. The electrode also includes an electrical connector, which is in electrical contact with the second major surface of the conductive substrate and protrudes from the conductive substrate.

[0005] In other embodiments, the electrode includes: a conductive substrate having a first major surface and a second major surface; a discontinuous layer of conductive particles, wherein at least some of the conductive particles include shaped particles having at least one point, and the conductive substrate encapsulates the conductive particles so that at least one point of at least one of the conductive particles protrudes from the second major surface of the conductive substrate; and an electrical connector in electrical contact with the second major surface of the conductive substrate, the conductive particles, or a combination thereof. The electrical connector protrudes from the conductive substrate.

[0006] In yet another embodiment, the dry electrode comprises: an electrical connector having a second major surface including an electrode plate portion and a first main portion including a head portion; and a discontinuous conductive particle layer that is in electrical contact with the second main portion of the electrical connector, and wherein the conductive particles comprise shaped particles having at least one point.

[0007] Also disclosed is a sheet product that can be used as a precursor for a dry electrode. In some embodiments, the sheet product includes: a substrate having a first major surface and a second major surface; a discontinuous layer of conductive particles, at least some of the conductive particles are in contact with the second major surface of the substrate, and the conductive particles include shaped particles having at least one point. The sheet product also includes a support layer, the support layer having a first major surface and a second major surface, wherein the first major surface of the support layer is in contact with the second major surface of the substrate, and the support layer encapsulates the conductive particles so that at least one point of at least one of the conductive particles protrudes from the second major surface of the support layer. In some embodiments, the substrate includes a conductive layer. In other embodiments, the support layer includes a conductive layer, and the substrate includes a non-conductive substrate.

[0008] Also disclosed is a method for preparing a dry electrode. In some embodiments, the method includes preparing a precursor sheet product, wherein preparing the precursor sheet product includes: providing a substrate having a first major surface or a second major surface; providing conductive particles, the conductive particles including shaped particles having at least one point; contacting at least one conductive particle with the second major surface of the substrate so that at least one point protrudes from the second major surface of the substrate; providing a support material layer having a first major surface and a second major surface; contacting the first major surface of the support material layer with the second major surface of the substrate and the conductive particles so that at least one point of at least one conductive particle protrudes through the second major surface of the support material layer. The method also includes contacting an electrical connector with a conductive substrate to form an electrical connection. In some embodiments, the substrate includes a conductive substrate. In other embodiments, the substrate includes a non-conductive substrate, and the support material layer includes a conductive layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] The present application may be more fully understood by referring to the following detailed description of various embodiments of the present disclosure in conjunction with the accompanying drawings.

[0010] Figure 1 is a cross-sectional view of an embodiment of the conductive particle of the present disclosure.

[0011] Figure 2 is a cross-sectional view of an embodiment of a dry electrode of the present disclosure.

[0012] Figure 3 is a cross-sectional view of another embodiment of the dry electrode disclosed herein.

[0013] Figure 4 is a cross-sectional view of another embodiment of the dry electrode disclosed herein.

[0014] Figure 5 is a cross-sectional view of an embodiment of the dry electrode of the present disclosure used on human skin.

[0015] Figure 6 It is a cross-sectional view of a sheet product capable of forming a dry electrode according to the present disclosure.

[0016] Figure 7 is a cross-sectional view of another embodiment of the dry electrode disclosed herein.

[0017] Figure 8 is a photograph showing shaped particles of the present disclosure.

[0018] Fig. 9 is a photograph showing the electrode prepared in Example 8.

[0019] In the following description of the illustrated embodiments, reference is made to the accompanying drawings and various embodiments in which the present disclosure may be practiced are shown in these drawings by way of example. It should be understood that the embodiments may be utilized and structural changes may be made without departing from the scope of the present disclosure. The figures are not necessarily drawn to scale. Like numbers used in the figures refer to like parts. However, it should be understood that the use of numbers to refer to parts in a given figure is not intended to limit the parts marked with the same numbers in another figure. DETAILED DESCRIPTION

[0020] Electrodes for measuring biopotentials are widely used in modern clinical and biomedical applications. These applications cover many physiological tests, including electrocardiogram (ECG), electroencephalogram (EEG), impedance tomography (EIT), electromyography (EMG), and electrooculography (EOG). Electrodes used for these types of physiological tests act as transducers by converting the electrical potential or biopotential in the body into a voltage that can be measured by conventional measuring and recording devices.

[0021] Generally, such electrodes are attached to the surface of the skin. The difficulty with placing electrodes on the surface of the skin is that the outer layer of the skin (stratum corneum) lacks moisture, and this lack of moisture creates a high impedance. The high impedance arises from the lack of ion mobility due to the lack of moisture in the stratum corneum.

[0022] The electrical conduction of the human body is based on the movement of ions rather than the movement of electrons present in metal conductors. In order to register the electronic signals from the human body, the electrodes must convert the ionic conduction into electronic conduction. The vast majority of electrodes available today achieve this transduction by using a silver / silver chloride reduction / oxidation reaction. + Ions and Cl -The ionic hydrogel wets the stratum corneum and enables ions to migrate between the skin and the electrode. Transduction occurs within the electrode at the interface of the hydrogel and the conductive material (usually a metal buckle or metal layer of a conductive carbon composite). The conductive material is coated with silver, enabling the following reversible reaction to occur and thus enabling detection of electrical impulses in the body.

[0023]

[0024]

[0025] One difficulty with using electrodes containing hydrogels is that the water in the hydrogel is subject to evaporation. Thus, when used, the hydrogel can lose water and become ineffective. Additionally, the loss of water from the hydrogel is a significant challenge in the storage and transportation of the electrode. To prevent the hydrogel from losing water before its use, expensive packaging (such as foil-lined envelopes) is often used to increase the limited storage life of such electrodes.

[0026] Therefore, considerable effort has been made to develop "dry" electrodes that do not use hydrogels. To make dry electrodes, many attempts have focused on the alternative of using hydrogels to hydrate the dry stratum corneum, that is, using small structures to penetrate the stratum corneum and access the more water-rich skin layers located below. Generally speaking, these structures are coated with materials (usually silver and silver chloride) that will form a reduction / oxidation couple in the presence of water. Examples of such small structures that have been used include microneedles or similar small pointed structures to penetrate the stratum corneum to deeper layers of the skin with more water, where ions are more mobile, thereby achieving conduction.

[0027] The methods of manufacturing these electrodes (usually involving injection molding or other similar processes followed by coating the resulting microneedle structure with a redox couple) are labor-intensive, relatively high-cost processes. These manufacturing issues confine dry electrodes to a niche market. Therefore, new processes are needed for preparing dry electrodes in an economical manner to allow these electrodes to compete in the market with relatively easy-to-produce wet electrodes.

[0028] In the present disclosure, a method of producing a dry electrode is described, which involves the use of micro-replicated particles that can be prepared in a continuous process. Such particles have been prepared for use in abrasive products and can be used to form skin permeable structures in electrode constructions. Further, these particles can be coated with redox materials in most processes. These coated particles are then coated on a conductive substrate to form a dry electrode. The formed dry electrode and the method of preparing the dry electrode are described in more detail below.

[0029] Unless otherwise indicated, all numbers used in the specification and claims to express structural dimensions, quantities and physical properties should be understood to be modified by the term "about" in all cases. Therefore, unless otherwise indicated, the numerical parameters listed in the above specification and the appended claims are approximate values, which can vary according to the desired properties sought to be obtained by those skilled in the art using the teachings disclosed herein. Numerical ranges expressed as end values ​​include all numbers contained in the range (such as 1 to 5 including 1, 1.5, 2, 2.75, 3, 3.80, 4 and 5) and any range within the range.

[0030] Unless the content clearly dictates otherwise, as used in this specification and the appended claims, the singular forms "a," "an," and "the" encompass embodiments having plural referents. For example, reference to "a layer" encompasses embodiments having one layer, two layers, or more layers. Unless the content clearly dictates otherwise, as used in this specification and the appended claims, the term "or" is generally used in a sense including "and / or."

[0031] As used herein, the term "adhesive" refers to a polymer composition that can be used to adhere two adherends together. Examples of adhesives are pressure sensitive adhesives and gel adhesives.

[0032] Those of ordinary skill in the art are well aware that pressure-sensitive adhesive compositions have properties including: (1) strong and lasting tack, (2) adhesion with finger pressure, (3) sufficient ability to be fixed to an adherend, and (4) sufficient cohesive strength to be cleanly removed from an adherend. It has been found that materials that work well as pressure-sensitive adhesives are polymers that are designed and formulated to exhibit the desired viscoelastic properties, thereby achieving a desired balance of tack, peel adhesion, and shear holding power. Achieving the proper balance of properties is not a simple approach.

[0033] As used herein, the term "gel adhesive" refers to a viscous semisolid cross-linked matrix containing a liquid or fluid capable of adhering to one or more substrates. Gel adhesives may have some properties in common with pressure-sensitive adhesives, but they are not pressure-sensitive adhesives. "Hydrogel adhesives" are gel adhesives that have water as the fluid contained within the cross-linked matrix.

[0034] The term "(meth)acrylate" refers to monomeric acrylate or methacrylate esters of alcohols. Acrylate and methacrylate monomers or oligomers are collectively referred to herein as "(meth)acrylates". Materials referred to as "(meth)acrylate-functional" are materials that contain one or more (meth)acrylate groups.

[0035] As used herein, the terms "shaped abrasive particles" and "shaped particles" are used interchangeably and refer to ceramic particles that can be used as abrasive particles, wherein at least a portion of the particle has a predetermined shape that is replicated by a mold cavity used to form the shaped precursor particles. The shaped particles will generally have a predetermined geometric shape that substantially replicates the mold cavity used to form the shaped particles. As used herein, shaped particles do not include abrasive particles obtained by a mechanical comminution operation.

[0036] The terms "room temperature" and "ambient temperature" are used interchangeably and refer to temperatures in the range of 20°C to 25°C.

[0037] The terms "Tg" and "glass transition temperature" are used interchangeably. If measured, Tg values ​​are determined by differential scanning calorimetry (DSC) at a scan rate of 10°C / minute unless otherwise indicated. Typically, Tg values ​​for copolymers are not measured, but rather calculated using the well-known Fox formula using the Tg values ​​of the monomers provided by the monomer supplier, as understood by those skilled in the art.

[0038] The present invention discloses a sheet product that can be used to make a dry electrode, a dry electrode, and a method for making a dry electrode. The sheet product described herein is a substantially continuous sheet comprising multiple layers of polymer material and non-polymer material, wherein the polymer layer and the non-polymer layer can be continuous or discontinuous. The advantage of preparing a sheet product that can be subsequently cut, formed or shaped into a dry electrode is the versatility and low cost of such a process relative to other options that can be used to make a dry electrode. A variety of dry electrodes can be prepared using the sheet product disclosed herein. In addition, as will be described in more detail below, the use of conductive shaped particles allows the direct formation of discrete dry electrodes and dry electrodes formed by the sheet product disclosed herein. In addition, discrete dry electrodes can be formed into arrays, and thereby a low-cost manufacturing process is again utilized.

[0039] A variety of sheet products can be prepared and used to form dry electrodes. Generally speaking, the sheet product includes a substrate layer, a support layer, wherein a discontinuous layer of conductive particles is surrounded by the support layer, wherein at least one point of the conductive particles protrudes from the support layer. A variety of materials can be used to prepare the sheet products of the present disclosure.

[0040] The sheet product includes a substrate layer. The substrate layer serves as a base on which the remainder of the sheet material can be assembled. A variety of substrate layers are suitable. In some embodiments, the substrate layer is a single layer, and in other embodiments, the substrate layer is a multilayer substrate.

[0041] In some embodiments, the substrate is a carrier layer, which means that the substrate is used in the preparation of the sheet product, but is not included as a permanent part of the sheet product, but is removed at a certain time. Examples of suitable carrier layers include a variety of polymer films. In some embodiments, the substrate includes a release liner. Release liners are well known in the adhesive field and include polymer films having inherent release properties or having a release coating on at least one surface.

[0042] In some embodiments, the substrate comprises a non-conductive substrate, such as the support layer described above, but the substrate is not removed from the electrode. Thus, the non-conductive substrate remains in the final product.

[0043] In other embodiments, the substrate includes a conductive substrate having a first major surface and a second major surface. The conductive substrate may include a single-layer structure or it may be a multilayer structure. If the conductive substrate is a multilayer structure, the second major surface of the multilayer structure is a conductive layer, so that the conductive particles are in electrical contact with the conductive layer. In some embodiments, the conductive substrate includes a two-layer structure with a conductive layer and a non-conductive layer. A variety of such conductive substrates are suitable. In some embodiments, the conductive substrate includes a film layer with a conductive coating, such as a polymer film layer. Examples of polymer films include films comprising one or more polymers, such as cellulose acetate butyrate; cellulose acetate propionate; cellulose triacetate; poly (meth) acrylates, such as polymethyl methacrylate; polyesters, such as polyethylene terephthalate and polyethylene naphthalate; copolymers or blends based on naphthalene dicarboxylic acid; polyether sulfone; polyurethane; polycarbonate; polyvinyl chloride; syndiotactic polystyrene; cycloolefin copolymers; and polyolefins, including polyethylene and polypropylene, such as cast and biaxially oriented polypropylene. The film may comprise a single layer or multiple layers, such as polyethylene terephthalate coated with polyethylene.A variety of conductive coatings are suitable, such as a thin coating of metal, a metal grid, or a continuous coating of conductive carbon.

[0044] The sheet article of the present disclosure also includes a discontinuous layer of conductive particles. By discontinuous layer is meant that the layer includes discrete particles that are not all in contact with each other.

[0045] A variety of conductive particles are suitable for use in the sheet products of the present disclosure. Generally speaking, the conductive particles include non-compressed shaped particles with a conductive metal coating. Typically, the conductive particles are prepared from particles prepared by a method for making shaped abrasive particles, but the conductive particles can have a variety of shapes, including shapes such as water chestnuts. The conductive metal coating can be a multilayer coating, for example, the conductive metal coating can cover the entire or substantially the entire surface of the shaped particles, and a secondary coating (such as a silver coating or a silver / silver chloride coating) can be selectively coated on all or a portion of the first conductive metal coating. In some embodiments, the conductive particles include particles that are completely coated with silver, and a portion of the coating is converted to a silver / silver chloride coating, or a portion of the silver coating can be coated with a silver chloride coating. In other embodiments, the particles are completely coated with a conductive coating, and then a portion of the particles is coated with silver and converted to a silver / silver chloride coating. Although various sizes and shapes are suitable for shaped particles, at least one dimension of the shaped particles is 100 microns to 1500 microns.

[0046] In some embodiments, the non-compressed shaped particles include ceramic shaped particles. Examples of suitable ceramic shaped particles are shaped abrasive particles with inclined sidewalls, as described in U.S. Patent No. 8,142,531. The steps for making shaped particles are described below. Shaped abrasive particles are particularly desirable for forming articles of the present disclosure because they can be mass-produced with known techniques and coated with a conductive coating to form particles having at least one point. These pointed conductive particles are non-compressible and can penetrate the stratum corneum when forming a dry electrode.

[0047] The first process step involves providing a seeded dispersion or a seedless dispersion that can be converted into alpha-alumina. The alpha-alumina precursor composition generally includes a liquid of a volatile component. The dispersion generally contains enough liquid to make the viscosity of the dispersion low enough to fill the mold cavity and replicate the mold surface, but the amount of liquid cannot be so much that the cost of subsequently removing the liquid from the mold cavity is too high. Boehmite or alumina hydrates other than boehmite can also be used. Boehmite can be prepared by known techniques or can be commercially obtained. Examples of commercially available boehms include products with the trademarks "DISPERAL" and "DISPAL" (both available from Sasol North America, Inc.) or "HiQ-40" (available from BASF Corporation). The dispersion may contain a modifying additive or a precursor of a modifying additive. The modifying additive can be used to enhance certain desired properties of the particles or to improve the efficiency of a subsequent sintering step. The dispersion may also contain a nucleating agent to enhance the conversion of hydrated alumina or calcined alumina to alpha-alumina. Nucleating agents suitable for use in the present disclosure include fine particles of alpha-alumina, alpha-iron oxide or its precursors, titanium dioxide and titanates, chromium oxide, or any other material that nucleates the transformant. If a nucleating agent is used, the amount should be sufficient to convert the alpha-alumina. For example, a process for nucleating such dispersions is disclosed in U.S. Patent No. 4,744,802 (Schwabel). A peptizing agent may be added to the dispersion to produce a more stable hydrosol or colloidal dispersion. Suitable peptizing agents are monoprotic acids or acidic compounds such as acetic acid, hydrochloric acid, formic acid, and nitric acid.

[0048] The dispersion may be formed by any suitable means, such as, for example, simply by mixing alumina monohydrate with water containing a peptizing agent, or by forming a slurry of alumina monohydrate and then adding a peptizing agent to the slurry. A defoamer or other suitable chemical may be added to reduce the tendency to form bubbles or entrain air during mixing. If desired, additional chemicals such as wetting agents, alcohols, or coupling agents may be added, as disclosed in U.S. Pat. No. 5,645,619 (Erickson et al.), U.S. Pat. No. 5,551,963 (Larmie), and U.S. Pat. No. 6,277,161 (Castro).

[0049] The second process step involves providing a mold having at least one mold cavity, and typically a plurality of cavities. The plurality of cavities may be formed in a production tool. The production tool may be a ribbon, a sheet, a continuous web, a coating roller (such as a rotogravure roller), a sleeve mounted on a coating roller, or a mold. The production tool comprises a polymeric material. Examples of suitable polymeric materials include thermoplastic materials such as polyesters, polycarbonates, polyethersulfones, poly(methyl methacrylate), polyurethanes, polyvinyl chloride, polyolefins, polystyrenes, polypropylenes, polyethylenes, or combinations thereof, or thermosetting materials.

[0050] The cavity has a defined three-dimensional shape. In an exemplary embodiment, the shape of the cavity can be described as quadrangular when viewed from the top, so that the particles formed have a tetrahedral shape. Alternatively, other cavity shapes can be used. The cavities of a given mold can have the same shape or different shapes.

[0051] The third process step involves filling the cavity in the mold with the dispersion by any conventional technique. In some embodiments, a knife roll coater or a vacuum slot die coater may be used. If desired, a release agent may be used to aid in removing the particles from the mold.

[0052] The fourth process step involves removing the volatile components to dry the dispersion. Advantageously, the volatile components are removed at a rapid evaporation rate. In some embodiments, the removal of the volatile components by evaporation is performed at a temperature above the boiling point of the volatile components. The upper limit of the drying temperature generally depends on the material from which the mold is made. For polypropylene molds, the temperature should be below the melting point of the plastic.

[0053] The fifth process step involves removing the precursor shaped particles from the mold cavity. The precursor shaped particles can be removed from the cavity by using the following processes, alone or in combination, on the mold: using gravity, vibration, ultrasonic vibration, vacuum or pressurized air to remove the particles from the mold cavity. The precursor particles can be further dried outside the mold. If the dispersion is dried to the desired degree in the mold, this additional drying step is unnecessary.

[0054] The sixth process step involves calcining the precursor shaped particles. During calcination, substantially all volatile materials are removed and the various components present in the dispersion are converted to metal oxides. Typically, the precursor shaped particles are heated to a temperature of 400° C. to 800° C. and maintained within this temperature range until free water and more than 90% by weight of any bound volatile materials are removed.

[0055] The seventh process step involves sintering the calcined precursor shaped particles to form alpha-alumina particles. Prior to sintering, the calcined precursor shaped particles are not fully densified and therefore lack the hardness required for use as shaped particles. Sintering is performed by heating the calcined precursor shaped particles to a temperature of 1000°C to 1650°C and maintaining them within this temperature range until substantially all of the monohydrated alpha-alumina (or equivalent) is converted to alpha-alumina and the porosity is reduced to less than 15% by volume. The length of time that the calcined precursor shaped particles must be exposed to the sintering temperature in order to achieve this level of conversion depends on a variety of factors, but is typically five seconds to 48 hours. After sintering, the shaped particles may have a Vickers hardness of 10 GPa, 16 GPa, 18 GPa, 20 GPa or more.

[0056] Other steps may be used to modify the described process, such as rapidly heating the material from the calcining temperature to the sintering temperature, centrifuging the dispersion to remove sludge, waste, etc. In addition, if desired, the present process may be modified by combining two or more of the process steps in the process steps. A more complete description of conventional process steps that may be used to modify the process of the present disclosure is provided in U.S. Pat. No. 4,314,827 (Leitheiser).

[0057] The steps outlined above are merely illustrative, and the present disclosure is not directed to the preparation of non-compressed ceramic particles, but rather to their use in new and unexpected ways to prepare sheet articles and dry electrodes.

[0058] The formed ceramic particles can be coated with metal using a variety of different techniques. Among the suitable methods are physical vapor deposition. Physical vapor deposition (PVD) describes a variety of vacuum deposition methods that can be used to produce thin films and coatings. PVD is characterized by a process in which a material changes from a condensed phase to a vapor phase and then back to a thin film condensed phase. The most common PVD processes are sputtering and evaporation.

[0059] Typically, ceramic particles are coated with silver using the methods and apparatus described in US Pat. Nos. 4,612,242 and 7,727,931 and US Patent Publication No. 2014 / 0363554.

[0060] The sheet article also includes a support layer. The support layer has a first major surface and a second major surface. The first major surface of the support layer contacts the second major surface of the substrate. The support layer encapsulates the conductive particles so that at least one point of at least one of the conductive particles protrudes from the second major surface of the support layer. Generally speaking, the thickness of the support layer is 25 microns to 500 microns, and in some embodiments is 50 microns to 150 microns.

[0061] In some embodiments, the support layer comprises a pressure sensitive adhesive layer.Pressure sensitive adhesives are very suitable support layers because they can be used to hold the conductive particles in place and also to adhere the formed dry electrode article to the skin of the user.

[0062] A variety of pressure-sensitive adhesives are suitable for use as the support layer. Useful pressure-sensitive adhesives include those based on natural rubber, synthetic rubber, styrene block copolymers, polyvinyl ethers, acrylic resins, polyalphaolefins, silicones, polyurethanes or polyureas.

[0063] Useful natural rubber pressure-sensitive adhesives typically comprise plasticized natural rubber, 25 to 300 parts of one or more tackifying resins per 100 parts of natural rubber, and typically 0.5 to 2.0 parts of one or more antioxidants. The grades of natural rubber range from pale white crepe grades to darker ribbed smoked rubber grades, including, for example, CV-60 (a controlled viscosity rubber grade) and SMR-5 (a ribbed smoked rubber grade).

[0064] Tackifying resins used with natural rubber typically include, but are not limited to, wood rosin and its hydrogenated derivatives; terpene resins of various softening points and petroleum-based resins, such as the "ESCOREZ 1300" series of C5 aliphatic olefin-derived resins from Exxon, and the "PICCOLYTE S" series of polyterpenes from Hercules, Inc. Antioxidants may be used to retard oxidative attack on natural rubber, which may result in loss of cohesive strength of natural rubber adhesives. Useful antioxidants include, but are not limited to, amines such as N-N'di-β-naphthyl-1,4-phenylenediamine, available under the trade name "AGERITE D"; phenols such as 2,5-di-(tert-amyl)hydroquinone, available under the trade name "SANTOVAR A" from Monsanto Chemical Co.; tetrakis[methylene-3-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate]methane, available under the trade name "IRGANOX 1010" from Ciba-Geigy Corp.; and 2-2'-methylenebis(4-methyl-6-tert-butylphenol), available under the trade name Antioxidant 2246; and dithiocarbamates such as zinc dithiodibutylcarbamate. Other materials may be added to the natural rubber adhesive for special applications, wherein the additives may include plasticizers, pigments, and curing agents for partially hardening the pressure sensitive adhesive.

[0065] Another class of useful pressure sensitive adhesives are those that include synthetic rubbers. Such adhesives are generally rubbery elastomers that are either self-tacky or non-tacky and require a tackifier.

[0066] Self-bonding rubber pressure-sensitive adhesives include, for example, butyl rubber (a copolymer of isobutylene and less than 3% isoprene), polyisobutylene (an isoprene homopolymer), polybutadiene (such as "TAKTENE 220 BAYER") or styrene / butadiene rubber. Butyl rubber pressure-sensitive adhesives typically contain antioxidants, such as zinc dibutyl dithiocarbamate. Polyisobutylene pressure-sensitive adhesives typically do not contain antioxidants. Synthetic rubber pressure-sensitive adhesives that typically require tackifiers are also typically easier to melt process. They contain polybutadiene or styrene / butadiene rubber, 10 to 200 parts of tackifier per 100 parts of rubber, and typically 0.5 to 2.0 parts of antioxidant per 100 parts of rubber, such as "IRGANOX 1010". An example of a synthetic rubber is "AMERIPOL 1011A", a styrene / butadiene rubber available from BF Goodrich. Useful tackifiers include rosin derivatives such as "FORAL 85" (a stabilized rosin ester from Hercules Inc.), the "SNOWTACK" series of rosins from Tenneco, and the "AQUATAC" series of tall oil rosins from Sylvachem; and synthetic hydrocarbon resins such as the "PICCOLYTE A" series of polyterpenes, the "ESCOREZ 1300" series of C5 aliphatic olefin derived resins, the "ESCOREZ 2000" series of C9 aromatic / aliphatic olefin derived resins and polyaromatic C9 resins such as the "PICCO 5000" series of aromatic hydrocarbon resins from Hercules, Inc. Other materials may be added for special applications, including hydrogenated butyl rubber, pigments, plasticizers, liquid rubber (such as "VISTANEXLMMH" polyisobutylene liquid rubber available from Exxon), and curing agents to partially vulcanize the adhesive.

[0067] Styrene block copolymer pressure-sensitive adhesives generally comprise AB-type elastomers or ABA-type elastomers, wherein A represents a thermoplastic polystyrene block and B represents a rubbery block of polyisoprene, polybutadiene or poly(ethylene / butylene) and a resin. Examples of various block copolymers that can be used in the block copolymer pressure-sensitive adhesive include linear, radial, star and tapered styrene-isoprene block copolymers, such as "KRATON D1107P" available from Shell Chemical Co., and "EUROPRENE SOL TE 9110" available from EniChem Elastomers Americas, Inc.; linear styrene-(ethylene-butylene) block copolymers, such as "KRATON G1657" available from Shell Chemical Co.; linear styrene-(ethylene-propylene) block copolymers, such as "KRATON G1750X" available from Shell Chemical Co.; and linear, radial and star styrene-butadiene block copolymers, such as "KRATON D1118X", and "EUROPRENE SOL TE 6205" available from EniChem Elastomers Americas, Inc. The polystyrene blocks tend to form spherical, cylindrical or lamellar domains, which give the block copolymer pressure-sensitive adhesive a two-phase structure. The resin associated with the rubber phase generally produces tack in the pressure-sensitive adhesive. Examples of rubber phase-associated resins include: aliphatic olefin-derived resins such as the "ESCOREZ 1300" series and the "WINGTACK" series available from Goodyear; rosin esters such as the "FORAL" series and "STAYBELITE" ester 10, both available from Hercules Inc.; hydrogenated hydrocarbons such as the "ESCOREZ 5000" series available from Exxon; polyterpenes such as the "PICCOLYTE A" series; and terpene phenolic resins derived from petroleum or turpentine sources such as "PICCOFYNA 100" available from Hercules, Inc. Resins associated with the thermoplastic phase tend to harden the pressure sensitive adhesive.Resins associated with the thermoplastic phase include polyaromatics, such as the "PICCO 6000" series of aromatic hydrocarbon resins available from Hercules Inc.; coumarone-indene resins, such as the "CUMAR" series available from Neville; and other high solubility parameter resins derived from coal tar or petroleum and having a softening point above about 85°C, such as the "AMOCO 18" series of alpha-methylstyrene resins available from Amoco, the "PICCOVAR 130" alkyl aromatic polyindene resin available from Hercules, Inc., and the "PICCOTEX" series of alpha-methylstyrene / vinyltoluene resins available from Hercules. Other materials may be added for special purposes, including rubber phase plasticizing hydrocarbon oils such as "TUFFLO 6056" available from Lyondell Petrochemical Co., polybutene-8 available from Chevron, "KAYDOL" available from Witco, and "SHELLFLEX 371" available from Shell Chemical Co.; pigments; antioxidants such as "IRGANOX 1010" and "IRGANOX 1076" both available from Ciba-Geigy Corp., "BUTAZATE" available from Uniroyal Chemical Co., "CYANOX LDTP" available from American Cyanamid, and "D-TEX® 371" available from Monsanto Co. Co.); antiozonants such as "NBC", a nickel dibutyl dithiocarbamate available from DuPont; liquid rubbers such as "VISTANEX LMMH" polyisobutylene rubber; and UV inhibitors such as "IRGANOX 1010" and "TINUVIN P" available from Ciba-Geigy Corp.

[0068] Polyvinyl ether pressure-sensitive adhesives are generally homopolymers of vinyl methyl ether, blends of vinyl ethyl ether or vinyl isobutyl ether, or blends of homopolymers of vinyl ether with copolymers of vinyl ether and acrylate to achieve the desired pressure-sensitive adhesive properties. Depending on the degree of polymerization, the homopolymer can be a viscous oil, a tacky soft resin, or a rubbery substance. Polyvinyl ethers used as raw materials in polyvinyl ether adhesives include polymers based on vinyl methyl ether, such as "LUTANOL M 40" available from BASF, and "GANTREZ M 574" and "GANTREZ 555" available from ISP Technologies, Inc.; vinyl ethyl ether, for example, "LUTANOLA 25", "LUTANOL A 50" and "LUTANOL A 100"; vinyl isobutyl ether, for example, "LUTANOL I30", "LUTANOL I60", "LUTANOL IC", "LUTANOL I60D" and "LUTANOL I 65D"; methacrylate / vinyl isobutyl ether / acrylic acid, such as "ACRONAL 550 D" available from BASF. Antioxidants that can be used to stabilize polyvinyl ether pressure-sensitive adhesives include, for example, "IONOX 30" available from Shell, "IRGANOX 1010" available from Ciba-Geigy, and "ZKF" available from Bayer Leverkusen. Other materials may be added for special purposes, including tackifiers, plasticizers, and pigments, as described in BASF literature.

[0069] Acrylic pressure-sensitive adhesives generally have a glass transition temperature of about -20°C or less and may contain from 100 weight percent to 80 weight percent of a C3-C 12Alkyl ester components, such as, for example, isooctyl acrylate, 2-ethylhexyl acrylate, and n-butyl acrylate, and polar components from 0 to 20 weight percent, such as, for example, acrylic acid, methacrylic acid, ethylene-vinyl acetate units, N-vinyl pyrrolidone, and styrene macromonomers. Generally speaking, acrylic pressure-sensitive adhesives contain 0 to 20 weight percent acrylic acid and 100 to 80 weight percent isooctyl acrylate. Acrylic pressure-sensitive adhesives can be self-adhesive or tacky. Useful tackifiers for acrylic resins are rosin esters such as "FORAL 85" available from Hercules Inc., aromatic resins such as "PICCOTEX LC-55WK", aliphatic resins such as "PICCOTAC95" available from Hercules Inc., and terpene resins such as α-pinene and β-pinene available under the trade names "PICCOLYTE A-115" and "ZONAREZ B-100" from Arizona Chemical Co. Other materials may be added for special purposes, including hydrogenated butyl rubber, pigments, and curing agents for partially vulcanizing the adhesive.

[0070] Polyalphaolefin pressure-sensitive adhesives, also known as poly (1-olefin) pressure-sensitive adhesives, generally include substantially non-crosslinked polymers or non-crosslinked polymers, which may have radiation-activated functional groups grafted thereon, as described in U.S. Patent No. 5,209,971 (Babu et al.). Polyalphaolefin polymers may be self-adhesive and / or include one or more tackifying materials. If non-crosslinked, the intrinsic viscosity of the polymer is generally between about 0.7 dL / g and 5.0 dL / g as measured by ASTM D 2857-93, "Standard Practice for Dilute Solution Viscosity of Polymers". In addition, polymers are generally mainly amorphous. Available polyalphaolefin polymers include, for example, C3-C 18 Poly(1-olefin) polymers, usually C5-C 12Alpha-olefins and copolymers thereof with C3 or C6-C8 and copolymers thereof with C3. Tackifying materials are generally resins miscible in poly-alpha-olefin polymers. The total amount of tackifying resin in poly-alpha-olefin polymers ranges from 0 to 150 parts by weight (according to specific applications) per 100 parts of poly-alpha-olefin copolymers. Available tackifying resins include resins, polyterpenes, synthetic polyterpenes, etc. obtained by polymerization of C5 to C9 unsaturated hydrocarbon monomers. Examples of such commercially available resins based on this type of C5 olefin fractions include "WINGTACK 95" and "WINGTACK 15" tackifying resins available from Goodyear Tire and Rubber Co. Other hydrocarbon resins include "REGALREZ 1078" and "REGALREZ 1126" available from Hercules Chemical Co. and "ARKO NP 115" available from Arakawa Chemical Co. Other materials may be added for special purposes and include antioxidants, fillers, pigments and radiation activated crosslinking agents.

[0071] Silicone pressure-sensitive adhesive includes two main components, i.e., polymer or gel and tackifying resin. Polymer is usually high molecular weight polydimethylsiloxane or polydimethyldiphenylsiloxane, which contains residual silanol functional groups (SiOH) at the end of the polymer chain, or a block copolymer comprising polydiorganosiloxane soft segments and urea or oxamide end-capped hard segments. Tackifying resin is generally a three-dimensional silicate structure terminated by trimethylsiloxy (OSiMe3) and also comprising some residual silanol functional groups. The example of tackifying resin includes SR 545 (derived from General Electric Company, Silicone Resins Division (GeneralElectric Co., Silicone Resins Division), Waterford, New York) and MQD-32-2 (derived from Shin-Etsu Silicones of America, Inc., Torrance, California). The manufacture of typical silicone pressure-sensitive adhesives is described in U.S. Patent No. 2,736,721 (Dexter). The manufacture of siloxane urea segmented copolymer pressure-sensitive adhesives is described in U.S. Patent No. 5,214,119 (Leir et al.). Other materials, including pigments, plasticizers and fillers, may be added for special purposes. The amount of filler is generally 0 to 10 parts per 100 parts of silicone pressure-sensitive adhesive. Examples of fillers that can be used include zinc oxide, silicon dioxide, carbon black, pigments, metal powders and calcium carbonate. A particularly suitable class of silicone-containing pressure-sensitive adhesives are those with oxamide-terminated hard segments, such as those described in U.S. Patent No. 7,981,995 (Hays) and U.S. Patent No. 7,371,464 (Sherman).

[0072] Polyurethane and polyurea pressure sensitive adhesives useful in the present disclosure include those disclosed, for example, in WO 00 / 75210 (Kinning et al.), and in US Pat. Nos. 3,718,712 (Tushaus), 3,437,622 (Dahl), and 5,591,820 (Kydonieus et al.).

[0073] Particularly useful pressure-sensitive adhesives are based on at least one poly(meth)acrylate (i.e., (meth)acrylic pressure-sensitive adhesives). Particularly desirable poly(meth)acrylates are derived from: (A) at least one monoethylenically unsaturated (meth)acrylate alkyl ester monomer (i.e., alkyl acrylate and alkyl methacrylate monomers); and (B) at least one monoethylenically unsaturated free radical copolymerized reinforcing monomer. The reinforcing monomer has a homopolymer glass transition temperature (Tg) higher than the homopolymer glass transition temperature of the (meth)acrylate alkyl ester monomer, and is a monomer that increases the glass transition temperature and cohesive strength of the resulting copolymer. Monomer A and monomer B are selected so that the copolymer formed therefrom is extrudable and capable of forming fibers. As used herein, "copolymer" refers to a polymer comprising two or more different monomers, including terpolymers, tetrapolymers, and the like.

[0074] Generally speaking, the monomers used to prepare the pressure-sensitive adhesive component of the fibers of the present invention include: (A) a monoethylenically unsaturated alkyl (meth)acrylate monomer that generally has a glass transition temperature (Tg) of no greater than about 0° C. when homopolymerized; and (B) a monoethylenically unsaturated free radical copolymerizable reinforcing monomer that generally has a glass transition temperature of at least about 10° C. when homopolymerized. The glass transition temperature of the copolymer of monomer A and monomer B can be measured by differential scanning calorimetry, but more typically, Tg is calculated using the well-known Fox equation using the homopolymer Tg value provided by the monomer supplier.

[0075] Monomer A, which is a monoethylenically unsaturated alkyl acrylate or alkyl methacrylate (i.e., (meth)acrylate), contributes to the flexibility and viscosity of the copolymer of the adhesive component of the fiber. Generally speaking, the homopolymer Tg of monomer A is not higher than about 0°C. Typically, the alkyl group of the (meth)acrylate has an average of about 4 to about 20 carbon atoms, and more generally, an average of about 4 to about 14 carbon atoms. The alkyl group may optionally contain an oxygen atom in the chain, thereby forming, for example, an ether or alkoxy ether. Examples of monomer A include, but are not limited to, 2-methylbutyl acrylate, isooctyl acrylate, lauryl acrylate, 4-methyl-2-pentyl acrylate, isopentyl acrylate, sec-butyl acrylate, n-butyl acrylate, n-hexyl acrylate, 2-ethylhexyl acrylate, n-octyl acrylate, n-decyl acrylate, isodecyl acrylate, isodecyl methacrylate, and isononyl acrylate. Other examples include, but are not limited to, polyethoxylated or polypropoxylated methoxy (meth)acrylates, such as CARBOWAX acrylates (commercially available from Union Carbide) and NK ester AM90G (commercially available from Shin Nakamura Chemical Co., Ltd., Japan). Particularly suitable monoethylenically unsaturated (meth)acrylates that can be used as monomer A include isooctyl acrylate, 2-ethylhexyl acrylate, and n-butyl acrylate. Combinations of various monomers classified as A monomers can be used to make copolymers for making the fibers of the present invention.

[0076] Monomer B as a reinforcing monomer of monoethylenically unsaturated free radical copolymerization increases the glass transition temperature and cohesive strength of the copolymer. Generally speaking, monomer B has a homopolymer Tg of at least about 10°C. Typically, monomer B is a reinforcing (meth) acrylic monomer, including acrylic acid, methacrylic acid, acrylamide or (meth) acrylate. Examples of monomer B include, but are not limited to, acrylamides, such as acrylamide, methacrylamide, N-methylacrylamide, N-ethylacrylamide, N-hydroxyethylacrylamide, diacetoneacrylamide, N,N-dimethylacrylamide, N,N-diethylacrylamide, N-ethyl-N-aminoethylacrylamide, N-ethyl-N-hydroxyethylacrylamide, N,N-dihydroxyethylacrylamide, tert-butylacrylamide, N,N-dimethylaminoethylacrylamide and N-octylacrylamide. Other examples of monomer B include itaconic acid, crotonic acid, maleic acid, fumaric acid, 2,2-(diethoxy)ethyl acrylate, 2-hydroxyethyl acrylate or methacrylate, 3-hydroxypropyl acrylate or methacrylate, methyl methacrylate, isobornyl acrylate, 2-(phenoxy)ethyl acrylate or methacrylate, biphenyl acrylate, tert-butylphenyl acrylate, cyclohexyl acrylate, dimethyladamantyl acrylate, 2-naphthyl acrylate, phenyl acrylate, N-vinylformamide, N-vinylacetamide, N-vinylpyrrolidone, and N-vinylcaprolactam. Preferred reinforcing acrylic monomers that can be used as monomer B include acrylic acid and acrylamide. Combinations of various reinforcing monoethylenically unsaturated monomers classified as B monomers can be used to make copolymers for making fibers of the present invention.

[0077] Generally, acrylate copolymers are formulated to have a resulting Tg of less than about 25° C., more typically less than about 0° C. Such acrylate copolymers typically contain from about 60 parts / 100 to about 98 parts / 100 of at least one monomer A and from about 2 parts / 100 to about 40 parts / 100 of at least one monomer B. In some embodiments, the acrylate copolymers have from about 85 parts / 100 to about 98 parts / 100 of at least one monomer A and from about 2 parts / 100 to about 15 parts / 100 of at least one monomer B.

[0078] If necessary, a cross-linking agent can be used to construct the molecular weight and strength of the copolymer of the adhesive. Generally, a cross-linking agent is a reagent copolymerized with monomer A and monomer B. A cross-linking agent can produce chemical cross-linking (e.g., covalent bonds or ionic bonds). Alternatively, a cross-linking agent can produce thermally reversible physical cross-linking, which is derived from, for example, the formation of enhanced domains caused by phase separation and / or acid / base interactions (i.e., functional groups in the same polymer or functional groups between polymers or functional groups between polymers and additives) of hard segments (i.e., Tg is higher than room temperature, preferably higher than those segments of 70°C). By using macromonomers (such as styrene macromonomers of U.S. Patent No. 4,554,324 (Husman)) or polymer ion cross-linking as described in WO99 / 42536, preferred cross-linking occurs. Suitable cross-linking agents are also disclosed in U.S. Patent No. 4,737,559 (Kellen), U.S. Patent No. 5,506,279 (Babu et al.) and U.S. Patent No. 6,083,856 (Joseph et al.).

[0079] In some embodiments, the support layer includes a multilayer construction. A variety of multilayer constructions are suitable. The multilayer construction may or may not include at least one layer of pressure-sensitive adhesive as described above. A particularly suitable multilayer construction is a transfer tape. Double-sided tape, also referred to as "transfer tape", is an adhesive tape having adhesive on both exposed surfaces. In some transfer tapes, the exposed surface is just the two surfaces of a single adhesive layer. Other transfer tapes are multilayer transfer tapes with at least two identical or different adhesive layers, and in some cases an intermediate layer of a non-adhesive layer. For example, the multilayer transfer tape may be a 3-layer construction with a first adhesive layer, an intermediate layer, and a second adhesive layer. The intermediate layer may provide handling and / or tear strength or other desired properties. In some embodiments of the sheet product of the present disclosure, the transfer tape includes a three-layer construction, which includes a first pressure-sensitive adhesive layer, a second pressure-sensitive adhesive layer, and a layer between the first pressure-sensitive adhesive layer and the second pressure-sensitive adhesive layer.

[0080] In the sheet articles of the present invention, transfer tapes are particularly suitable support layers because they are free-standing articles and can be easily laminated to a substrate. In the present disclosure, the conductive particles can be placed on the second major surface of the substrate, and the transfer tape can be laminated to the substrate so that the first major surface of the transfer tape contacts the second major surface of the substrate. In this process, during lamination of the transfer tape, at least some of the conductive particles protrude through the second major surface of the transfer tape. Typically, at least one point of the shaped particles protrudes from 50 microns to 1000 microns from the first major surface of the support layer.

[0081] In embodiments where the substrate is a conductive substrate, the support layer may be a single layer of adhesive or a multilayer transfer tape. In embodiments where the substrate is not a conductive substrate, the support substrate includes a conductive layer. In some embodiments, a transfer tape is used as the support layer, and the center layer of the transfer tape is a conductive layer.

[0082] The above-mentioned sheet products can be used to form the dry electrodes described herein. A plurality of different embodiments of the dry electrodes are described. The embodiments formed by the above-mentioned sheet products can be divided into two general electrode configurations. The first general configuration includes a conductive substrate, a discontinuous conductive particle layer, a support layer, and an electrical connector. The second general electrode configuration is related to the first general configuration and includes a conductive layer, a discontinuous conductive particle layer, and an electrical connector. Each of these configurations is described in detail below.

[0083] In some embodiments of the first configuration, the dry electrode comprises: a conductive substrate having a first major surface and a second major surface; a discontinuous conductive particle layer, wherein at least some of the conductive particles are in contact with the second major surface of the conductive substrate; and a support layer having a first major surface and a second major surface, wherein the first major surface of the support layer is in contact with the second major surface of the conductive substrate; and an electrical connector, which is in electrical contact with the second major surface of the conductive substrate. The conductive particles include shaped particles having at least one point. In this embodiment, the support layer encapsulates the conductive particles so that at least one point of at least one of the conductive particles protrudes from the second major surface of the support layer.

[0084] The dry electrode includes a conductive substrate. The conductive substrate is used as a supporting layer for the conductive particles described below. A variety of conductive substrates are suitable and have been described above. In some embodiments, the conductive substrate includes a film layer with a conductive coating, such as a polymer film layer. Examples of polymer films include films comprising one or more polymers, such as cellulose acetate butyrate; cellulose acetate propionate; cellulose triacetate; poly (meth) acrylates, such as polymethyl methacrylate; polyesters, such as polyethylene terephthalate and polyethylene naphthalate; copolymers or blends based on naphthalene dicarboxylic acid; polyether sulfone; polyurethane; polycarbonate; polyvinyl chloride; syndiotactic polystyrene; cycloolefin copolymers; and polyolefins, including polyethylene and polypropylene, such as cast and biaxially oriented polypropylene. The film may include a single layer or multiple layers, such as polyethylene terephthalate coated with polyethylene. A variety of conductive coatings are suitable, such as a thin coating of a metal, a metal grid, or a continuous coating of conductive carbon.

[0085] The dry electrode also includes a discontinuous layer of conductive particles. By discontinuous layer is meant that the layer includes discrete particles that are not all in contact with each other. The conductive particles are described in detail above.

[0086] The first general electrode configuration includes a support layer. The support layer has a first major surface and a second major surface. The first major surface of the support layer contacts the second major surface of the conductive substrate. In this embodiment, the support layer encapsulates the conductive particles so that at least one point of at least one of the conductive particles protrudes from the second major surface of the support layer. Generally speaking, the thickness of the support layer is 25 microns to 500 microns, and in some embodiments is 50 microns to 150 microns.

[0087] Suitable support layers are described in detail above. In the dry electrode of the present invention, transfer tapes are particularly suitable support layers because they are self-supporting articles and can be easily laminated to a substrate. In the present disclosure, the conductive particles can be placed on the second major surface of the conductive substrate, and the transfer tape can be laminated to the conductive substrate so that the first major surface of the transfer tape contacts the second major surface of the conductive substrate. In this process, during the lamination of the transfer tape, at least some of the conductive particles protrude through the second major surface of the transfer tape. Typically, at least one point of the shaped particles protrudes from the first major surface of the support layer by 50 microns to 1000 microns.

[0088] The dry electrode further includes an electrical connector which is in electrical contact with the second major surface of the conductive substrate and protrudes from the conductive substrate.

[0089] A variety of electrical connectors are suitable for use in the dry electrodes of the present disclosure. Essentially any electrical connector suitable for use with a wet electrode or a dry electrode is suitable for use in the present dry electrodes. Examples include the connector stud described in U.S. Patent No. 6.415,170 (Loutis et al.). The stud has an electrode plate portion located on one side of the substrate of the dry electrode for electrically connecting to the skin of the wearer of the dry electrode through a conductive substrate and conductive particles. On the other side of the electrical connector is a head portion to which an electrical device can be attached. The head portion can have a variety of shapes and sizes.

[0090] A second general electrode configuration is also disclosed herein. The second general electrode configuration is related to the first general configuration and includes a conductive layer, a discontinuous conductive particle layer, and an electrical connector. This embodiment is similar to the first general electrode configuration described above, but in this embodiment, the conductive substrate and the support layer of the first general configuration are combined in a single element (conductive layer) rather than two different elements. This general electrode configuration can also be prepared from the sheet products described above. Suitable sheet products for forming these dry electrodes are those in which the support layer includes a conductive layer and the substrate includes a non-conductive substrate.

[0091] In some embodiments of the second general electrode configuration, the dry electrode includes a conductive layer having a first major surface and a second major surface, a discontinuous conductive particle layer, and an electrical connector. The conductive layer can be a single layer, but as described below, typically includes other non-conductive layers and is therefore a multilayer structure. In this embodiment, at least some of the conductive particles include shaped particles having at least one point, and the conductive layer encapsulates the conductive particles so that at least one point of at least one of the conductive particles protrudes from the second major surface of the conductive layer. The electrical connector is in electrical contact with the second major surface of the conductive layer, the conductive particles, or a combination thereof, and the electrical connector protrudes from the first major surface of the conductive layer.

[0092] A variety of materials can be used as the conductive layer, as long as the layer is conductive and can encapsulate the discontinuous conductive particle layer. Typically, the thickness of the conductive layer is 25 microns to 500 microns.

[0093] In some embodiments, the conductive layer comprises a multilayer structure. An especially suitable multilayer structure is a transfer tape. The transfer tape has been described above. An example of a transfer tape suitable for use as a conductive layer is a three-layer structure, which comprises a first pressure-sensitive adhesive layer, a second pressure-sensitive adhesive layer, and a conductive interlayer between the first pressure-sensitive adhesive layer and the second pressure-sensitive adhesive layer. In this embodiment, conductive particles are embedded in the second pressure-sensitive adhesive layer and are electrically contacted with the conductive interlayer of the transfer tape, and an electrical connector is embedded in the first pressure-sensitive adhesive layer and is electrically contacted with the conductive interlayer of the transfer tape.

[0094] The particles and electrical connectors suitable for the second general configuration of the electrode are the same as those described above for the first general configuration of the electrode.As with the first general electrode, at least one point of the shaped particle protrudes from the second major surface of the conductive layer by 50 microns to 1000 microns.

[0095] Also disclosed herein is a dry electrode that can be prepared from conductive particles but not from a sheet product, but a discrete dry electrode can be prepared directly. In these embodiments, a dry electrode can be formed by adhering a discontinuous conductive particle layer to the electrode plate portion of an electrical connector. Conductive particles and electrical connectors are described above.

[0096] This embodiment can be prepared by contacting and adhering the conductive particles to the electrode plate portion of the electrical connector. A variety of techniques and materials can be used to adhere the conductive particles to the electrical connector, as long as an electrical connection can be maintained between the conductive particles and the electrical connector. Conductive adhesives can be used to adhere the conductive particles to the electrical connector. The electrode plate of the electrical connector can be coated with a conductive adhesive to form a continuous or discontinuous conductive adhesive layer on the electrode plate portion. The conductive particles can then be contacted with the coated electrode plate portion. In other embodiments, the conductive particles can be adhered to the electrical connector by welding or similar techniques (such as heating the electrical connector to a temperature at which the conductive coating of the conductive particles softens and a conductive interaction is formed between the conductive particles and the electrical connector). As described above, although this embodiment describes the formation of discrete dry electrodes, these techniques can also be used to form discrete dry electrode arrays. The formation of discrete dry electrode arrays allows mass production of these electrodes.

[0097] It may be desirable to add additional elements to the discrete configuration to form a dry electrode. For example, since electrical connectors are typically relatively small, a base layer may be attached to the configuration to provide a larger electrode that is easier to handle. Additionally, a support layer as described above may be added to the configuration. As with the previously described configuration, at least one point of at least one conductive particle protrudes through the support layer. These additional elements provide support and ease of handling for the dry electrode.

[0098] Also disclosed herein are methods for preparing dry electrodes. A variety of methods are suitable. As described above, in some embodiments, the method involves preparing a sheet article and using the sheet article to prepare a dry electrode. These methods vary depending on whether the prepared dry electrode is a first general electrode configuration or a second general electrode configuration. In addition, discrete dry electrodes can be directly prepared without first preparing a sheet article.

[0099] In some embodiments, a method of forming a dry electrode includes forming a precursor sheet article, wherein the precursor sheet article includes a general method, and the precursor sheet article can be made into an electrode by adding an electrical connector. The method is generally used to prepare two general electrode configurations. The general method of preparing an electrode includes: providing a substrate having a first major surface and a second major surface; providing conductive particles; contacting at least one conductive particle with the second major surface of the substrate so that at least one point protrudes from the second major surface of the substrate; providing a supporting material layer having a first major surface and a second major surface; contacting the first major surface of the supporting material layer with the second major surface of the substrate and the conductive particles so that at least one point protrudes through the second major surface of the supporting material layer.

[0100] Conductive particles include shaped particles having at least one point, as described in detail above. In the method where the dry electrode includes a first general configuration, the substrate includes a conductive substrate. The conductive substrate has been described in detail above. The method also includes contacting an electrical connector with the conductive substrate to form an electrical connection. The conductive substrate may be a multilayer configuration. In some embodiments, the conductive substrate includes a two-layer configuration, wherein the conductive layer forms the second major surface of the substrate, and the non-conductive layer forms the first major surface of the substrate.

[0101] In these embodiments, the supporting material comprises the above-mentioned supporting layer. In some embodiments, the supporting material layer comprises a pressure-sensitive adhesive layer. The pressure-sensitive adhesive can be provided as a liquid or a solution, and is applied to the conductive substrate layer comprising a discontinuous conductive particle layer. Then, if the pressure-sensitive adhesive layer is dissolved in the solvent, it can be dried, if the pressure-sensitive adhesive layer provides in a molten form, it can be allowed to solidify, or if the pressure-sensitive adhesive layer provides as an uncured composition, it can be solidified. The pressure-sensitive adhesive can also be provided as a preformed pressure-sensitive adhesive layer laminated to the conductive substrate layer, and the conductive substrate layer comprises a discontinuous conductive particle layer. However, the pressure-sensitive adhesive is applied to the conductive substrate layer comprising a discontinuous conductive particle layer, and at least some of the points of the particles of the discontinuous layer protrude through the pressure-sensitive adhesive layer.

[0102] In addition, as mentioned above, the supporting material layer may include a multilayer structure. The example of a suitable multilayer structure is a transfer tape, wherein the transfer tape includes a three-layer structure, and the three-layer structure includes the first pressure-sensitive adhesive layer, the second pressure-sensitive adhesive layer and the layer between the first pressure-sensitive adhesive layer and the second pressure-sensitive adhesive layer. The transfer tape in these embodiments may also include a release liner contacted with the second pressure-sensitive adhesive layer. The method comprising a transfer tape or a supporting layer of similar type includes contacting the first major surface of the supporting material layer with the second major surface and the conductive particles of substrate. In the embodiment where the supporting layer is a three-layer transfer tape, the step includes: the first pressure-sensitive adhesive layer is laminated to the second major surface and the conductive particles of substrate, and applying pressure to the release liner of the laminated transfer tape so that the point of the conductive particles is pressed through the transfer tape, and removing the release liner to expose the protruding point of the second pressure-sensitive adhesive and the conductive particles.

[0103] Regardless of the composition of the support layer or how it is formed, the support layer has a suitable thickness to allow at least one point of the conductive particles to protrude through the second major surface of the support layer. Typically, the support layer has a thickness of 10 microns to 500 microns.

[0104] Other embodiments of the method of the present disclosure relate to preparing a dry electrode of the second general configuration. These embodiments also relate to the use of a preformed sheet product, but the elements of the sheet product are different from the elements in the sheet product precursor described above. In these embodiments, the substrate comprises a non-conductive substrate, and the supporting material layer comprises the conductive layer described above. The non-conductive substrate may be a removable substrate. A removable substrate refers to a substrate that is not incorporated into the final dry electrode, but is used as a carrier on which conductive particles are placed. Examples of removable substrates include release liners as described above. In other embodiments, the non-conductive substrate is not a removable substrate, but remains as part of the final product. Typically, the non-conductive substrate comprises a polymer film. Examples of suitable polymer films include films comprising one or more polymers such as cellulose acetate butyrate; cellulose acetate propionate; cellulose triacetate; poly(meth)acrylates such as polymethyl methacrylate; polyesters such as polyethylene terephthalate and polyethylene naphthalate; copolymers or blends based on naphthalene dicarboxylic acids; polyethersulfones; polyurethanes; polycarbonates; polyvinyl chloride; syndiotactic polystyrene; cycloolefin copolymers; and polyolefins, including polyethylene and polypropylene, such as cast and biaxially oriented polypropylene. The film may include a single layer or multiple layers, such as polyethylene terephthalate coated with polyethylene.

[0105] As mentioned above, the supporting material layer comprises a conductive layer. Suitable conductive layer has been described in detail above. The conductive layer may be a monolayer or it may be a multilayer structure. The formation of the conductive layer may be realized by laminating the transfer tape to the second major surface of the substrate and a discontinuous conductive particle layer. In other embodiments, curable or flowable material may be applied to the second major surface of the substrate and a discontinuous conductive particle layer. If the coating is curable, the coating may be cured, or the coating may be allowed to cool and harden when the coating is able to flow, with the prerequisite being that the coating is conductive when solidifying or cooling. In some embodiments, the conductive layer comprises a pressure-sensitive adhesive, but the conductive layer need not be an adhesive layer. In the embodiment where the conductive layer comprises an adhesive, the conductive layer may be a conductive adhesive, or it may be a multilayer structure, such as the transfer tape comprising the conductive layer.

[0106] As with the method for making a dry electrode of the first general configuration, the method for making a dry electrode of the second general configuration further includes contacting an electrical connector with the conductive layer and / or the conductive particles to form an electrical connection.

[0107] Regardless of the composition of the support layer or how it is formed, the support layer has a suitable thickness to allow at least one point of the conductive particles to protrude through the second major surface of the support layer. Typically, the support layer has a thickness of 10 microns to 500 microns.

[0108] If the substrate is a removable substrate, the removable substrate can be removed before or after the electrical connector contacts the conductive layer and / or conductive particles to form an electrical connection. The surface exposed by removing the removable substrate can be left as an open surface, or a different substrate can be adhered to the surface if desired.

[0109] The embodiments of the present disclosure can be further understood by referring to the drawings.

[0110] Figure 1 is a cross-sectional view of an embodiment of a shaped conductive particle of the present disclosure. Figure 1 In FIG. 1 , shaped conductive particle 100 has a conductive coating 110 on the entire particle and a secondary conductive coating 120 on only a portion of the particle.

[0111] Figure 2 One embodiment of the dry electrode disclosed in the present invention is shown. Figure 2 In the embodiment, the dry electrode 200 has conductive particles 201, a support layer 230, and the support layer has three sub-layers 231, 232, and 233, wherein 231 and 233 are adhesive layers and 232 is a film layer. Layer 240 is a conductive substrate including a conductive layer 241 and an optional film layer 242. An electrical connector 250 is in electrical contact with the conductive substrate 240.

[0112] Figure 3 is another embodiment of the dry electrode disclosed herein, and is similar to Figure 2 The dry electrode shown. Figure 3 In the embodiment, the dry electrode 300 has conductive particles 301 , an integral support layer 330 , a conductive substrate 340 including a conductive layer 341 and an optional film layer 342 , and an electrical connector 350 .

[0113] Figure 4 is yet another embodiment of the dry electrode disclosed herein. Figure 4 In the embodiment, dry electrode 400 has conductive particles 401 and support layer 430, which has three sublayers 431, 432, 433, where 431 and 433 are adhesive layers and 432 is a conductive layer. Layer 442 is a non-conductive substrate layer. Layer 442 is shown as a whole layer, but can be a multi-layer structure. Electrical connector 450 is in electrical contact with conductive layer 432.

[0114] Figure 5 The dry electrode 500 of the present disclosure is used in a manner that shows conductive particles 501 that penetrate the stratum corneum 570 and contact the epidermis 580 but do not reach the dermis 590. The dry electrode 500 can be any of the dry electrodes with electrical connector 550 shown above.

[0115] Figure 6This is an embodiment of the sheet product capable of forming a dry electrode disclosed in the present invention. Figure 6 In the embodiment, the sheet product 600 has conductive particles 601, a support layer 630, a base layer 640 having a conductive layer 641 and a film layer 642. It should be understood that in some embodiments, the base layer 640 is a non-conductive base layer and can be a whole layer or multiple layers. Similarly, the support layer 630 can be a multi-layer structure and include a conductive layer in some embodiments.

[0116] Figure 7 is another embodiment of the dry electrode of the present disclosure, in this example a discrete dry electrode. Figure 7 , a dry electrode 700 has conductive particles 701 adhered to an electrical connector 750 at a surface 702. Surface 702 may be a conductive adhesive layer, a solder connection, or the like.

[0117] Figure 8 is a photograph showing shaped conductive particles on a substrate layer.

[0118] Fig. 9 To show the above Figure 7 and photographs of shaped conductive particles on an electrical connector as described in Example 8 below.

[0119] Example

[0120] These examples are for illustrative purposes only and are not intended to limit the scope of the appended claims. Unless otherwise indicated, all parts, percentages, ratios, etc. in the examples and the remainder of the specification are by weight. Unless otherwise indicated, the solvents and other reagents used were obtained from Sigma-Aldrich Chemical Company, St. Louis, MO.

[0121] Production of Precision Shaped Grain (PSG) Tetrahedrons

[0122] Ceramic tetrahedra are produced according to the process outlined in U.S. Pat. No. 8,142,531. Alpha-alumina particles are made from a dispersion of alumina monohydrate that is gelled, molded, dried, calcined, and then sintered. In this case, a mold with multiple regular tetrahedral polymer cavities is used to shape the sol-gel, resulting in particles with edges approximately 33 mils (0.84 mm) long after sintering.

[0123] The boehmite sol-gel samples were made using the following recipe: Alumina monohydrate powder (1600 parts) sold under the trade name DISPERAL (available from CONDEA Chemie GmbH, Hamburg, Germany) was dispersed into a solution containing water (2400 parts) and 70% aqueous nitric acid (72 parts) by high shear mixing for 5 minutes. The resulting sol-gel was aged for at least one hour before coating. The sol-gel was forced into a production tool having a tetrahedral mold cavity. The sol-gel was forced into the cavity with a putty knife so that the opening of the production tool was filled. A release agent (0.2% peanut oil in methanol) was used to coat the production tool, with approximately 0.1 mg / in 2 of peanut oil was applied to the production tool. Methanol was evaporated from the production tool prior to coating the sol-gel. The sol-gel coated production tool was left to dry overnight at room temperature. The precursor tetrahedral particles were removed from the production tool by passing them over an ultrasonic horn. The precursor tetrahedral particles were calcined at approximately 650°C and then saturated with a mixed nitrate solution of the following concentrations (reported as oxides): 1.8% each of MgO, Y2O3, Nd2O3 and La2O3. Excess nitrate solution was removed and the saturated precursor tetrahedral particles with openings were dried, then the particles were calcined again at 650°C and sintered at approximately 1400°C. Both calcination and sintering were performed in a tubular rotary kiln. The tetrahedral particles formed by this process had edges approximately 33 mils (0.84 mm) long after sintering.

[0124] Preparation of silver-coated PSG alumina particles by physical vapor deposition

[0125] Metallized particles are produced by using physical vapor deposition (PVD), including magnetron sputtering. For example, PVD methods for metallized particles are disclosed in U.S. Patent Nos. 4,612,242 and 7,727,931. The apparatus used in the following preparation of silver-coated PSG particles is described in published U.S. Patent Application No. 2014 / 0363554.

[0126] Forty cubic centimeters (41.45 g) of the PSG tetrahedrons prepared above were loaded into the particle stirrer in the vacuum chamber apparatus. The vacuum chamber was evacuated to 2×10 -05Torr, and then 125 sccm (standard cubic centimeters per minute) of argon was admitted. The sputtering process was initiated using an Ag (3" round) target. The sputtering power was 0.75 kW, and the process pressure was 13 mTorr. During the sputtering process, the PSG tetrahedron was flipped at 14 rpm. After 2 hours, the sputtering process was stopped, the chamber was vented, and the silver-coated tetrahedron was removed from the particle agitator. The density of the silver-coated tetrahedron particles was 4.1 g / cc, and the estimated Ag weight percentage was 3.8.

[0127] Conversion of silver to silver chloride

[0128] A portion of the Ag on the particle surface is converted to AgCl by a redox reaction in an aqueous solution of 0.03% NaO2Cl and 2% KCl. The target AgCl conversion rate is selected, and tetrahedrons with 10%-50% AgCl based on the initial Ag content are produced. The mass of Ag in each sample is calculated using the mass of the coated tetrahedron to be converted and the Ag mass fraction of the coated tetrahedron. Each mole of NaO2Cl converts 4 moles of Ag into AgCl. The coated tetrahedron is added to the solution and stirred intermittently for about 30 minutes. The tetrahedron is then filtered, washed 3 times with water, and then dried.

[0129] Assembling dry electrodes

[0130] For each dry electrode embodiment, a backing of 3M RED DOT ELECTRODE 9650 (available from 3M Company, St. Paul, MN) was used as the conductive substrate. The backing is a polyester film coated with a continuous conductive carbon layer. A 2 cm wide silver strip was printed on top of the carbon, separated by a 0.9 cm uncoated carbon strip.

[0131] To fabricate dry electrodes, Ag / AgCl coated tetrahedrons were dropped from a height of approximately 1 cm and randomly settled on a conductive substrate. The number of tetrahedrons per electrode is provided in Table 1 and is reported as "number of dots".

[0132] A 2.8 mil (71 micron) thick tackified acrylic transfer adhesive (LONGTERM WEAR ADHESIVE 4075, available from 3M Company, St. Paul, MN) was laminated to the nonwoven polyurethane backing of LONGTERM WEAR TAPE 4077 (also available from 3M Company, St. Paul, MN). After removing the liner covering the 4077 adhesive, a 0.75" (19 mm) wide strip of this construction was laminated to the particles distributed on the conductive substrate. A hand-held rubber roller (1.5" (3.8 cm) diameter, 1.88" (4.8 cm) length) was used to force the top of the tetrahedron through the adhesive layer, nonwoven backing, and paper release liner on the 4075 transfer adhesive by passing over the strip 3 to 5 times with approximately 20 pounds of pressure.

[0133] The electrode backing was cut parallel to the adhesive tape and 5 mm from its edge. The resulting tape strip was cut perpendicular to its length at 0.75" (19 mm) intervals to provide square electrodes with 5 mm tabs of exposed conductive base.

[0134] Example

[0135] Examples 1 to 3 were produced using tetrahedrons with a side length of 33 mils (0.84 mm). The tetrahedrons were coated with approximately 3.8% by weight silver, and 30% of the silver was converted to silver chloride. Each dry electrode measured 0.75 inches (1.9 cm) by 0.75 inches (1.9 cm) and had a 5 mm wide conductive connection tab on one side to facilitate electrical connection. Samples were made at a range of tetrahedral particle densities, and the number of particle points that penetrated the release liner was counted at 10X magnification. Electrodes with the same number of points were paired, and a range of point densities were tested.

[0136] Remove the release liner from the matched electrode pair. The electrode pair is placed on the leg of a male volunteer at a spacing of 4 inches (10.2 cm), and is pressed into place with moderate finger pressure for about one second. The impedance between the electrodes is measured using an EIM-105-10Hz pre-detection electrode impedance meter (General Devices, Inc., Indianapolis, IN, Indiana). For the application of each electrode, a new site is used. For each electrode pair, the distance between the centers remains constant at 4 inches (10.2 cm). Table 1 presents the results of the electrode pairs in which each electrode has a different number of tetrahedrons. The "number of points" in Table 1 indicates the number of points (tetrahedrons) on each electrode in the electrode pair. As a control, RED DOT 2670 hydrogel-based electrodes (3M Company, St. Paul, MN, Minnesota) are used and are referred to as Comparative Example 1.

[0137] Comparative Example 1 shows typical performance of an electrode comprising a hydrogel, which has a high initial impedance that decreases as the stratum corneum absorbs water from the hydrogel. The low initial impedance of Examples 1 to 3 relative to the initial impedance of Comparative Example 1 indicates that the dots have penetrated the stratum corneum, bypassing the high impedance that would be attributed to the low water content of the stratum corneum. (The stratum corneum typically contains 5% to 20% water. The epidermis into which the tetrahedron penetrates contains 60% to 70% water.)

[0138] Based on 8 points is almost as effective as 30 points, so a large number of penetrators is not required to achieve relatively low impedance.

[0139] The stability of the impedance values ​​of Examples 1 to 3 over the first three hours is an improvement over the changing impedance of Comparative Example 1. The changing impedance as the stratum corneum absorbs more and more water from the hydrogel can affect the measurements made with the electrodes.

[0140] Table 1 : Electrode impedance measurements (kilo-ohms, measured with an AC meter at 10 Hz) over time for electrodes with different numbers of Ag / AgCl coated tetrahedral sites per electrode.

[0141]

[0142] Examples 4-7 were prepared by the above method and tested on human subjects, but with varying levels of silver to silver chloride conversion. The data reported in Table 2 show that tetrahedrons with AgCl percentages ranging from 10% to 50% produced electrodes with acceptable performance.

[0143] Table 2: Electrode impedance (kilo-ohms) measurements over time for electrodes with different percentages of tetrahedron The ratio of Ag coating to AgCl .

[0144]

[0145] Example 8

[0146] A thin layer of solder paste (CHIP QUIK Solder Paste No Clean Sn42 / Bi57.6 / Ag0.4, from CHIP QUIK) is spread on the skin contact side of an electrical connector, similar to, for example, those shown as elements 250, 350, 450, or 550. Silver-coated tetrahedrons having a 30% AgCl conversion, prepared as described above, are placed on the solder paste. The coated electrical connector is then heated to above the curing temperature of the solder paste and allowed to cool, thereby producing an electrode comprising an electrical connector having silver / silver chloride-coated tetrahedrons attached to its surface, which is Figure 7 is schematically shown in Fig. 9 A photograph of the electrode is shown in .

[0147] These electrodes were tested on the skin of human subjects, and their electrical performance was compared with electrodes comprising untreated electrical connectors. The electrode pairs were placed on the skin with a spacing of about 4 inches (10 cm), and in the case where the electrode included an electrical connector with a silver / silver chloride-coated tetrahedron attached to its surface, the tetrahedron was in contact with the skin. Skin impedance was tested using an EIM-105-10Hz pre-test electrode impedance meter. For electrodes comprising untreated electrical connectors, impedance readings were above the detection limit of the instrument (>200 kilo-ohms). For electrodes comprising an electrical connector with a silver / silver chloride-coated tetrahedron attached to its surface, impedance readings were about 151 kilo-ohms after contacting the skin for 10 seconds. Electrodes comprising an electrical connector with a silver / silver chloride-coated tetrahedron welded to the skin contact side showed improved electrical performance.

Claims

1. A method for preparing a dry electrode, the method comprising: Preparing a precursor sheet product, wherein preparing the precursor sheet product comprises: providing a substrate having a surface, the surface comprising a carbon layer and silver strips disposed on the carbon layer, the silver strips being separated by uncoated carbon strips; Preparing conductive particles, wherein the preparation comprises: forming ceramic tetrahedrons, each ceramic tetrahedron including at least one apex; coating the ceramic tetrahedron with silver by a physical vapor deposition process including magnetron sputtering; and converting a portion of the silver coated on the ceramic tetrahedron into silver chloride through a redox reaction; distributing the conductive particles on the surface of the substrate; laminating a layer of support material to the surface of the substrate and to the conductive particles; Passing the tips of the conductive particles through the support material layer so that the tips of the conductive particles extend a certain distance from the support material layer to penetrate the stratum corneum of the user's skin but do not reach the dermis; At least one dimension of the conductive particles is in a range of 175 microns to 1500 microns. The method of claim 1 , wherein the substrate comprises a conductive substrate. 3 . The method of claim 2 , further comprising contacting an electrical connector with the conductive substrate to form an electrical connection. The method according to claim 2 , wherein the support material layer comprises a pressure-sensitive adhesive layer or a transfer tape. 5 . The method of claim 1 , wherein the substrate comprises a non-conductive substrate and the layer of support material comprises a conductive layer. 6 . The method according to claim 5 , further comprising contacting an electrical connector with the conductive layer and / or the conductive particles to form an electrical connection. 7 . The method of claim 4 , wherein causing the tips of the conductive particles to penetrate the support material layer comprises causing the tips of the conductive particles to penetrate the support material layer using a roller.

Citation Information

Patent Citations

  • Ethylene removal agent

    US20140363554A1

  • Polyurethane-based pressure-sensitive adhesives

    US3437622A

  • Pressure-sensitive adhesives based on cyclic terpene urethane resin

    US3718712A

  • Non-fused aluminum oxide-based abrasive mineral

    US4314827A

  • Acrylate copolymer pressure-sensitive adhesive composition and sheet materials coated therewith

    US4554324A